ASSESSMENT OF BIODIVERSITY OF CARABID BEETLES (COLEOPTERA, CARABIDAE) OF THE TSHETSHEN ISLAND IN THE СASPIAN SEA - I. A. Belousov; I. I. Kabak; G. M. Abdurakhmanov; G. M. Mukhtarova; G. M. Nakhibasheva (Юг России: экология, развитие, 2017)
Aim, material. Biodiversity of carabid beetles (Coleoptera, Carabidae) is studied for the Tshetshen Island in the Caspean Sea based on examination of 32799 adults belonging to 123 species collected during two seasons.Results. Five collecting sites on the Tshetshen Island were sampled and compared with data from the Nordovyi and Tiulenyi islands as well as from coastal areas of Dagestan. Carabid species composition of the Tshetshen Island differs in having a higher fraction of desert taxa. In this respect, it resembles more that of the Middle Asia and Kalmykia. Some species, common in the mainland, are not found on the island. Rank-abundance distributions, biodiversity indices and effective numbers of species were used to quantitify differences among collecting sites. In most cases, the data obtained fit the best to the Zipf-Mandelbrot distribution. Numbers of carabid species in sites ranged from 45 to 89. Despite of variation, the richness indices are shown to be significantly lower for the Tshetshen Island. This conclusion was confirmed using rarefaction curves. Decomposition of γ-diversity into its α- and β- components in terms of effective numbers of species has shown that α-diversity of carabids in mainland areas exceeds that of the Tshetshen Island only marginally while β-diversity is significantly higher. Cluster analysys of distance matrices has shown that the carabid assemblages of the Tshetshen Island are the most poor and specific, those from the coastal areas – the most species-rich while those of the Tiulenyi and Nordovyi islands are intermediate.Conclusion. Carabid assemblages of each island in the Caspian Sea may be considered as a rather randomly impoverished subset from the regional species pool of the Middle Asia and Caspian lowland.